Pneumomediastinum and pneumopericardium, a rare complication of asthma: a case report - Velásquez Marulanda, Milena (2025)
Pneumomediastinum is a relatively uncommon condition characterized by the presence offree air in the mediastinum that is not caused by surgery, a medical procedure, or trauma.An infrequent cause of pneumomediastinum is an asthma attack; furthermore, in certain situations, the air that reaches the mediastinum can spread to the pericardium and generate a pneumopericardium. The objective of this article is to document the clinical presentation, diagnosis, and treatment of pneumomediastinum and pneumopericardium in the context of an asthma exacerbation, aiming to provide healthcare professionals with tools to accuratelymanage these patients. To illustrate this, we present the case of a male patient who developedpneumomediastinum and pneumopericardium during an asthma attack.